SCORE performance in Central and Eastern Europe and former Soviet Union: MONICA and HAPIEE results - Vikhireva, Olga; Pajak, Andrzej; Broda, Grazyna; Malyutina, Sofia; Tamosiunas, Abdonas; Kubinova, Ruzena; Simonova, Galina; Skodova, Zdena; Bobak, Martin; Pikhart, Hynek (European heart journal, 2014)
AIMS: The Systematic COronary Risk Evaluation (SCORE) scale assesses 10 year risk of fatal atherosclerotic cardiovascular disease (CVD), based on conventional risk factors. The high-risk SCORE version is recommended for Central and Eastern Europe and former Soviet Union (CEE/FSU), but its performance has never been systematically assessed in the region. We evaluated SCORE performance in two sets of population-based CEE/FSU cohorts. METHODS AND RESULTS: The cohorts based on the World Health Organization MONitoring of trends and determinants in CArdiovascular disease (MONICA) surveys in the Czech Republic, Poland (Warsaw and Tarnobrzeg), Lithuania (Kaunas), and Russia (Novosibirsk) were followed from the mid-1980s. The Health, Alcohol, and Psychosocial factors in Eastern Europe (HAPIEE) study follows Czech, Polish (Krakow), and Russian (Novosibirsk) cohorts from 2002-05. In Cox regression analyses, the high-risk SCORE ≥5% at baseline significantly predicted CVD mortality in both MONICA [n = 15 027; hazard ratios (HR), 1.7-6.3] and HAPIEE (n = 20 517; HR, 2.6-10.5) samples. While SCORE calibration was good in most MONICA samples (predicted and observed mortality were close), the risk was underestimated in Russia. In HAPIEE, the high-risk SCORE overpredicted the estimated 10 year mortality for Czech and Polish samples and adequately predicted it for Russia. SCORE discrimination was satisfactory in both MONICA and HAPIEE. CONCLUSION: The high-risk SCORE underestimated the fatal CVD risk in Russian MONICA but performed well in most MONICA samples and Russian HAPIEE. This SCORE version might overestimate the risk in contemporary Czech and Polish populations.
Keywords: dospělí; Sex Distribution; hodnocení rizik; Female; rozložení podle pohlaví; Mortality; Adult; Risk prediction; ženské pohlaví; SCORE risk function; lidé; Litva; Cardiovascular risk factors; Risk Assessment; mortalita; prognóza; kohortové studie; Humans; Cohort Studies; Atherosclerosis; Central and Eastern Europe; Age Distribution; Lithuania; Male; Aged; Czech Republic; Russia; věkové rozložení; Cardiovascular mortality; Prognosis; ateroskleróza; Česká republika; lidé středního věku; senioři; mužské pohlaví; Poland; Middle Aged; Former Soviet Union; Rusko; Polsko